Maximizing electro‐optic performances in the fringe‐field switching liquid crystal mode with negative dielectric anisotropic liquid crystal. Issue 11 (13th November 2015) - Lim, Young Jin; Kim, Jin Hyun; Choi, Han Sol; Lee, Byeong Hoon; Kim, Dae Hyung; Kundu, Sudarshan; Jung, Jun Ho; Lee, Seung Hee; Bos, Philip J.
Abstract: The fringe‐field switching (FFS) mode that uses liquid crystals (LCs) with negative dielectric anisotropy is used in high‐resolution FFS liquid crystal display owing to its higher transmittance over positive LC, although its response time becomes slow and operating voltage ( Vop ) becomes high. In the device, reduction of the cell gap is required to achieve fast response time, which results in increase in Vop in general. In this paper, we propose the FFS mode with electrode width 1 µm and distance between the electrodes 1.5 µm. In such an electrode structure, Vop decreases with decreasing cell gap to 2 µm so that a proper Vop, high LC's light efficiency of 90%, a high color temperature, and a fast response time less than 10 ms, can be achieved, which maximizes electro‐optic performance of the FFS mode. Abstract : In the case of LC cell with w = 3 and l = 4.5, when the cell gap (d) reduced from 4 to 2 µm, overall light efficiency of LC dropped by 16% because of rapid decrement in light transmittance through the center of pixel and counter electrodes as well as at both edges of pixel electrodes. However, when w = 1 µm and l = 1.5 µm, maximum transmittance was noticed, irrespective of the cell gap.